Antidepressant-like effects of embelin and its possible mechanisms of action in chronic unpredictable stress-induced mice. (3rd August 2018) - Wang, Bailing; Chen, Xiaoqin; Zhou, Tiantian; Wang, Xiaoying
Abstract: Objectives Embelin, a principal active constituent of embelin ribes burm, has good therapeutic effects on various diseases. To explore the effects and underlying mechanisms of embelin on depression, we made a preliminary study to clarify this issue. Methods We first used chronic unpredictable stress (CUS) to construct the model of depression in mice. Then, we determined the effects of embelin on CUS-induced behavioral dysfunction using open field test, sucrose preference test, tail suspension test and forced swimming test. Furthermore, we used the biological experiments to evaluate the changes of brain-derived neurotrophic factor (BDNF), oxidative stress, neuronal inflammation and the hypothalamic pituitary adrenal (HPA) axis after embelin treatment. Results The behavioral tests indicated embelin indeed had efficient antidepressant effects. Moreover, enhanced BDNF expression, decreased oxidative stress markers (TBARS, nitric oxide) activities, elevated antioxidants (total thiol, catalase) expression, decreased pro-inflammatory cytokines (IL-6, TNF-α, IL-1β and COX-2) expression and normalized the HPA axis activity were found after embelin treatment in CUS-induced mice. Hence, the results of biological experiments confirmed the antidepressant-like effects of embelin. Discussion These results indicated that embelin can effectively suppress CUS-induced depressive-like behaviors through increasing BDNF expression, preventing brain from oxidative stress and neuronal inflammation, and normalizing the HPA activity.